The Role of Entitlement in Formatting Preferences Across Requesters and Recipients. Issue 7 (8th August 2020) - Trott, Sean; Rossano, Federico
ABSTRACT: Requesting plays a key role in human communication. One can request the same thing in multiple ways (e.g., "Pass the salt" vs. "Could you pass the salt?"). How do speakers determine which request form to produce? And how does this choice affect a recipient's evaluation of a request? Previous analyses of naturalistic conversations suggest that a speaker's entitlement – their expectations that the recipient of a request is able and willing to fulfill it – can influence their formatting decisions. However, the role of entitlement in format selection has not been tested experimentally, nor is it known how a requester's entitlement impacts a recipient's evaluation of a request form. Across several online experiments, we asked whether manipulations of a speaker's entitlement influenced formatting preferences across requesters and recipients. While requesters robustly recognized normative mappings between entitlement and request formatting (Experiment 2), they did not necessarily follow these mappings unprompted (Experiments 1–1b); instead, they tended to produce modal interrogative requests ("Can you do X?"), regardless of entitlement. Recipients, however, systematically modulated their preferences for particular forms as a function of a requester's entitlement (Experiment 3). We also conducted exploratory analyses on the data from each experiment using human-normed judgments about entitlement and other social-interactional variables (e.g., degree of imposition ); critically, for both Experiments 2 and 3, judgments about a requester's entitlement explained variance in participants' responses above and beyond other variables.